Banking in transition countries - John Bonin; Iftekhar Hasan; Paul Wachtel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
Modern banking institutions were virtually non-existent in the planned economies of cen-tral Europe and the former Soviet Union. In the early transition period, banking sectors began to develop during several years of macroeconomic decline and turbulence accompa-nied by repeated bank crises. However, governments in many transition countries learned from these tumultuous experiences and eventually dealt successfully with the accumulated bad loans and lack of strong bank regulation. In addition, rapid progress in bank privatiza-tion and consolidation took place in the late 1990s and early 2000s, usually with the partic-ipation of foreign banks. By 2005, the banking sectors in many transition countries had developed sufficiently to provide a wide range of services with solid bank performance. Recently, banks have switched their focus from lending to enterprises in a somewhat un-derdeveloped institutional environment to new collateralized lending to households, which accounts for much of the recent growth of credit in many transition countries.
URN:NBN:fi:bof-201408071914
Keywords: G21; P30; P34; P52; 330; transition banking; bank privatization; foreign banks; bank regulation; credit growth